PENGARUH PEMBERIAN PACLOBUTRAZOL DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERONG UNGUi(Solanum melongena L.): Paclobutrazol, Pupuk Kandang Ayam, Tanaman Terong Ungu - TRI MELIANA; Triyono, Kharis; Sumarmi, Sumarmi (innofarm, 2024)
The purpose of this study is to determine the optimal dose of paclobutrazol for purple eggplant growth and yield, to identify the best dosage of chicken manure for purple eggplant growth and yield, and to assess the interaction of paclobutrazol and chicken manure on purple eggplant growth and yield (Solanum melongena L). The second factor was the application of chicken manure, which was divided into three levels: K0 = No chicken manure at all, 0 tons/ha; K1 = 20 tons/ha; and K2 = 40 tons/ha. The best growth results, with a plant height of 55.33 cm and 60.67 leaves, were obtained by applying 200 ppm paclobutrazol and 640 g of chicken manure per plant. Additionally, the same combination produced the best yield results with 10.00 fruits per plant, a fruit weight of 288.22 g, and a harvest weight per plot of 8.70 kg. The application of chicken manure and paclobutrazol significantly impacted every measurable aspect of purple eggplant growth and yield..